2021
DOI: 10.3389/fmicb.2021.650773
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Genetic Clade of Cowpea Mild Mottle Virus and Characterization of Its Interaction With Soybean Mosaic Virus in Co-infected Soybean

Abstract: Cowpea mild mottle virus (CPMMV; genus Carlavirus) can be a destructive pathogen of soybean but there is little information about its distribution on soybean in China. Here, we collected soybean plants with virus-like symptoms from 11 fields widely scattered within China, and used high-throughput sequencing to determine their virome. Most samples (8/11) were co-infected by the well-studied potyvirus soybean mosaic virus (SMV) and CPMMV, and the remaining three samples were singly infected with CPMMV. The near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…In a previous study of SMV isolates from different soybean-growing areas in China, we identified isolate SMV_JL_GZL (SMV GZL ) that causes leaf crinkling of soybean and clusters separately from other Chinese SMV isolates in phylogenetic analyses (Wei et al 2021). We now report another SMV isolate, SMV_ZJ_NB (SMV NB ), which causes severer symptoms and accumulates virions in plants to a greater extent than SMV GZL .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In a previous study of SMV isolates from different soybean-growing areas in China, we identified isolate SMV_JL_GZL (SMV GZL ) that causes leaf crinkling of soybean and clusters separately from other Chinese SMV isolates in phylogenetic analyses (Wei et al 2021). We now report another SMV isolate, SMV_ZJ_NB (SMV NB ), which causes severer symptoms and accumulates virions in plants to a greater extent than SMV GZL .…”
Section: Introductionmentioning
confidence: 80%
“…SMV NB and SMV GZL isolates caused different symptoms on soybean SMV_ZJ_NB (SMV NB ), an isolate of SMV newly obtained from soybean in Ningbo, China, was compared with isolate SMV_JL_GZL (SMV GZL , GenBank Access no. MW354946.1) that had been obtained from northeast China through high-throughput sequencing (HTS) in a previous study (Wei et al 2021). Both isolates were inoculated to soybean cv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A severe mosaic pattern appeared on healthy leaves of Cowpea seedling after the inoculation. The same mechanically inoculation process for other virus has been previously reported by (Ali et al, 2020;Wei et al, 2021). During the present study, the infected samples were collected, then an ELISA test was performed for the confirmation of SMV and CMV.…”
Section: Resultsmentioning
confidence: 67%
“…It was first reported to infect cowpea in Ghana but was then found to infect legumes and other crops across the world (Brunt and Kenten, 1973). Recent studies have shown that CPMMV is also widely distributed in China, causing severe damage to soybean yields (Wei et al, 2021). The CPMMV genome has six ORFs, which encode an RNA-dependent RNA polymerase protein (RdRp), triple gene block proteins (TGBp1, p2, and p3), coat protein (CP), and a cysteine-rich protein with nucleic acid binding activity (CRP) (Menzel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%